2008
DOI: 10.1111/j.1471-4159.2008.05416.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐synaptic and post‐synaptic localization of EphA4 and EphB2 in adult mouse forebrain

Abstract: The ephrin receptors EphA4 and EphB2 have been implicated in synaptogenesis and long‐term potentiation in the cerebral cortex and hippocampus, where they are generally viewed as post‐synaptic receptors. To determine the precise distribution of EphA4 and EphB2 in mature brain synapses, we used subcellular fractionation and electron microscopy to examine the adult mouse forebrain/midbrain. EphA4 and EphB2 were both enriched in microsomes and synaptosomes. In synaptosomes, they were present in the membrane and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 48 publications
(136 reference statements)
9
81
0
Order By: Relevance
“…EphA4 receptors are highly expressed in brain structures with marked synaptic plasticity such as the hippocampus [14], and electron microscopy studies have shown that these receptors are basically localized on dendritic spines of hippocampal pyramidal neurons as well as on axon terminals [20,44]. Activation of EphA4 receptors is necessary for remodeling of CA1 dendritic spines in processes of synaptic plasticity in the adult brain [45][46][47], and EphA4 null mice have hippocampal distorted spines, confirming that EphA4 is required to maintain normal spine architecture in vivo [14,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EphA4 receptors are highly expressed in brain structures with marked synaptic plasticity such as the hippocampus [14], and electron microscopy studies have shown that these receptors are basically localized on dendritic spines of hippocampal pyramidal neurons as well as on axon terminals [20,44]. Activation of EphA4 receptors is necessary for remodeling of CA1 dendritic spines in processes of synaptic plasticity in the adult brain [45][46][47], and EphA4 null mice have hippocampal distorted spines, confirming that EphA4 is required to maintain normal spine architecture in vivo [14,48].…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of Eph receptor subtypes in synaptic plasticity has been demonstrated in numerous studies [17][18][19]. EphA4 and EphB2 are the two Eph receptors most intensively studied in the adult brain, where they have been detected in many regions, especially in the neocortex and hippocampus [20,21]. The multiple pathways involved in the regulation of synaptic function after Eph receptor activation remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EphB2 copurifies with both presynaptic active zones and the postsynaptic density fraction (14). To identify whether a presynaptic EphB receptor mediates eB-dependent presynaptic induction, we used a modified coculture assay (9) in which axons expressing shRNA targeting potential presynaptic receptors are cocultured with eB expressing HEK293T cells (9).…”
Section: Ephrin-b3 Controls Synapse Density Through Competitive Cell-mentioning
confidence: 99%
“…The present study also showed that the staining of PTPRO overlapped with that of EphA4 in the GL, EPL, and GCL of the adult mouse OB. Eph receptors are thought to regulate the reorganization of the actin cytoskeleton through Rho-family small G proteins (Huot, 2004), and they are known to regulate synaptogenesis Bouvier et al, 2008). Thus, PTPRO might participate in the regulation of synapse formation of OB interneurons through modulation of ephrin-Eph signaling.…”
Section: Discussionmentioning
confidence: 99%